Microbial quality of drinking water from selected food centers in the University of the Philippines Diliman campus - Alabado, Ferlinda Gatuz; Azanza, Ma. Patricia V. (1999)
The main objective of this study was to determine the microbial quality of drinking water from some selected food centers in the University of the Phillipines (UP), Diliman Campus. The test food centers included the College of Arts and Sciences Alumni Association (CASAA) food court, UP Cooperative (UP Coop) Canteen and three private food service units in the UP Shopping Center (SC). Analyses of the microbial and physico-chemical qualities of drinking water samples from these food centers were done. The microbial and physico-chemical characteristics were then compared to standards set by the Philippine National Standards (PNS) for Drinking Water (DOH 1993). The identification of the possible sources of contamination in the water samples tested was done through microbial examinations of water-contact surfaces such as the spout of the water dispenser, water pitchers and some drinking glasses. The surveillance standards for surface contamination in food services used in New Jersey, USA (Solberg et al. 1990) were used as reference values. Results of the microbiological analyses showed that the drinking water from food centers in the campus had a total plate and coliform counts ranging from < 10^3 to 10^10 cfu/100mL and <2 - 4 MPN/100mL, respectively. For the total plate count (TPC), only the drinking water samples form Baroque's canteen had TPCs within the standard limit of < 10^3 cfu/100mL. The coliform counts of all water samples were within the standard limit of <2 MPN/100mL, except for some drinking water samples from UP Coop canteen. The physic-chemical tests showed that the drinking water samples had turbidity readings that ranged from 0.42 to 3.30 NTU; hardness of 0.00-1.52 mg CaCO3/L and; residual chlorine of 0.01-0.49 mg/L. All the values for the physico-chemical parameters were within the standard values of 5.00 NTU for turbidity; 300 mg CaCO3/L for hardness and; 0.20 - 0.50 mg/L for residual chlorine, except for the residual chlorine values of some water samples from the CASAA food court, UP Coop canteen, Baroque's canteen and Papercup canteen. Only the water samples from Rodic's canteen had a residual chlorine values that were within the standard limit. Based on the microbial analyses of water-contact surfaces performed, it was found out that the spout of water dispensers in food centers in the campus had total plate and coliform counts which were 1.3 - 5.2 x 10^4 cfu/cm^2 and <0.002 - 0.24 MPN/cm^2, respectively. The water dispensers of CASAA food court and Baroque's canteen were those with TPCs within the acceptable limit of <4 cfu/cm^2. The drinking glasses had total plate and coliform counts of <0.01-4.7 cfu/cm^2 and <0.009-0.01 MPN/cm^2, respectively. The drinking glasses from UP Coop canteen, Baroque's canteen and Papercup canteen had TPCs beyond the acceptable limit of <1.0 cfu/cm^2. The study considered that the contamination of the drinking water samples from the food centers in UP Campus may come from the distribution lines due to possible formation of biofilm bacteria on pipe walls. Other sources of contamination could be the inadequacy in the treatment of water supplies and the poor system of handling and dispensing of drinking water in these test food service centers.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Drinking water -- Microbiology